Caracterização e análise de expressão dos genes das enzimas Arginase 1, Arginase 2 e Óxido Nítrico Sintase Induzível (iNOS) de Piaractus mesopotamicus em resposta à infecção por Aeromonas dhakensis - Carriero, Mateus Maldonado (2016)
The main goal of the present work was to perform an expression analysis of the Arg1, Arg2 and iNOS genes in the liver, anterior kidney and spleen of pacu (Piaractus mesopotamicus) in 4 different times post-infection, in response to the experimental infection with the bacterium Aeromonas dhakensis. The strain used in the present study was isolated from a specimen of P. mesopotamicus from the CEPTA/ICMBio in Pirassununga – SP, characterized by biochemical tests using the VITEK 2 automated identification system, and identified as belonging to the genus Aeromonas. Further molecular analyses of the 16S rRNA, gyrB and rpoD genes showed that the isolated strain belonged to the species A. dhakensis, a species that had never been reported in South America. This strain was resistant to the antibiotics ampicillin, ampicillin/sulbactam, cefoxitin and meroponem, with a high virulence level against experimentally infected pacus, causing clinical signs of acute hemorrhagic septicemia. The fifty per cent lethal dose (LD50) was 1.1 × 105 CFU/fish. Once characterized, this A. dhakensis strain was used in the infection experiments in P. mesopotamicus in order to analyze the expression of the Arg1, Arg2 and iNOS genes. These genes were sequenced and, from the partial sequences, P. mesopotamicus specific primers were designed for the quantitative real time PCR (qPCR) expression analyses. Following the infection with A. dhakensis, the Arg1 gene expression levels decreased in the kidney 24 h post-infection; the Arg2 gene expression of reduced in the liver at 12 h and 24 h post-infection and increased in the spleen at 24 h and 48 h post-infection; the gene expression of iNOS was significantly increased in she spleen at 12 h, 24 h, and 48 h post-infection. The results of the present study showed that the Arg2 and iNOS genes were the most variable in response to the A. dhakensis infection, indicating that these are involved in the initial immune response to bacterial infections in P. mesopotamicus. The organ that was most involved in this response was the spleen, which showed the highest levels of variation in these genes after the challenge. This is the first study assessing the expression levels of the Arg1, Arg2 and iNOS genes in P. mesopotamicus following the infection with A. dhakensis, providing a valuable contribution for the understanding of the immune response mechanisms against bacterial pathogens in this important South American fish species.